Analyzing the Relationship Between Transformational and Transactional Leadership Style on Employee Performance in Direktorat Jenderal Pajak Jawa Barat I - Widayanti, Anindya Tiara; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2015)
Abstract. In this century, the business worlds become more competitive. Both private and public organization should be able to organize and process all of the resources effectively and efficiently to get optimum performance (Hasibuan, 2004). Douglas (1996) explained that a company needs employees who has high performance, so it can help company to achieve its goals. In private company such as PT. TX Bandung, maximum employee performance is needed because it can help company to be develop. One of the factors that can motivate employees and increase their performance is the leadership style of the leader. Organization needs a leader who is capable to get their vision and mission together. Researcher interested to analyze the relationship between transformational and transactional leadership, which have impact to the employee performance. The objective of this research is to find the relationship between transformational and transactional to employee performance and to find the significant relationship between those variables. The result of the analysis shows that transformational and transactional leadership style has positive relationship to the employee performance. Transformational and transactional leadership also has significant effect to employee performance, either partially or concurrently. This study recommends that leader in the office have to increase their attitude in encouraged, motivated, gives supports and recognition, and providing rewards to the subordinates. Thus, employees are expected to become more optimal in performing the jobs.Ã‚Â Keywords: Transformational Leadership, Transactional Leadership, Employee Performance